2019
DOI: 10.1080/02601370.2019.1574923
|View full text |Cite
|
Sign up to set email alerts
|

Transformative and emancipatory literacy to empower

Abstract: This paper draws on sociological and critical educational frames, particularly Bourdieu's concept of symbolic violence, in order to contest the dominant model of literacy education that is driven by the premise of a 'knowledge economy'. Instead it foregrounds the political, social, and economic factors that marginalise learners. Data from two projects: an ethnographic study in a Further Education (FE) College in England and a study of community-based literacy programmes in Scotland, are probed to show how lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…While acknowledging the importance of literacy skills for everyday life and work, literacy scholars writing in the vein of the New Literacy Studies have demonstrated the socially situated nature of literacy and the ways in which literacies are learned and enacted within socio-cultural contexts and relationships (Barton andHamilton 1998, Duckworth andTett 2019;Grotl€ uschen et al, 2019a). This might include literacy sponsors and supporters (Brandt 1998, Buddeberg 2019, mediators (Papen 2010, Thompson 2015, Th eriault 2016 and networks and communities of practice (Fingeret 1983, Littlejohn et al 2012.…”
Section: Framing Literaturementioning
confidence: 99%
“…While acknowledging the importance of literacy skills for everyday life and work, literacy scholars writing in the vein of the New Literacy Studies have demonstrated the socially situated nature of literacy and the ways in which literacies are learned and enacted within socio-cultural contexts and relationships (Barton andHamilton 1998, Duckworth andTett 2019;Grotl€ uschen et al, 2019a). This might include literacy sponsors and supporters (Brandt 1998, Buddeberg 2019, mediators (Papen 2010, Thompson 2015, Th eriault 2016 and networks and communities of practice (Fingeret 1983, Littlejohn et al 2012.…”
Section: Framing Literaturementioning
confidence: 99%
“…I think those who are grappling with the ripple effects of the standardization push can learn from the work of the literacy researchers, grounded in community contexts, who have critiqued the impact of literacy frameworks. Their calls to resist their disempowering effects are important for understanding how literacies should reflect and support people's lives rather than dictating to them what they need to know (Duckworth & Tett, 2019;Tett, Hamilton & Crowther, 2012).…”
Section: Information Literacy: Definitions and Issuesmentioning
confidence: 99%
“…This is an opportunity for further contextualizing and renewing the decolonizing potential of Freirean approaches (Giroux, 1993). Duckworth and Tett's (2019) application of Freirean culture circles is also helpful for identifying the ways creativity can be used by learners to examine their lives and experiences.…”
Section: Knowledge and Powermentioning
confidence: 99%
See 2 more Smart Citations